Household heterogeneity, nonseparable preferences, and the Taylor principle - Babette Jansen; Roland Winkler (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2024)
We consider a two-agent New Keynesian model with savers and hand-to-mouth households with quasi-separable utility functions as introduced by Bilbiie (2020a). This framework allows for separate parameterization of consumption-hours complementarity and income effects on labor supply. We examine how variations in the size of income effects, the degree of non-separability between consumption and hours worked, and the share of hand-to-mouth households impact aggregate dynamics and determinacy properties of interest rate rules. Complementarity between consumption and hours worked and small income effects can reverse the Taylor principle and result in expansionary monetary contractions.
Keywords: E32; E52; E58; E44; E24; 330; Heterogeneity; Monetary policy; Nonseparable preferences; Real indeterminacy; Taylor principle; TANK